Profile of Neuromyth in Neuroscience Lectures and Its Relation to the Multiple Intelligence of PIAUD Students - Maryanti, Sri; Hartati, Sri; Agustin, Mubiar (Jurnal Pendidikan Raudhatul Athfal, 2024)
This study analyzes the profile of Neuromyth in Neuroscience lectures at PIAUD based on students' multiple intelligences. Neuromyths are misconceptions about the brain in learning. Early childhood education is very important as a stimulation of children's brain development. Teachers and prospective early childhood teachers need to avoid misconceptions about the brain (Neuromyths). This study is a descriptive research with a quantitative approach with the aim of identifying and describing neuromyths and the relationship of multiple intelligences of Early Childhood Islamic Education (PIAUD) students. The respondents to the study were 73 PIAUD students consisting of 95.9% women and 4.1% men with a pre-undergraduate education background. As many as 58.9% of the students who were used as respondents had taught 41.1%, had never taught 59.9%. Data was collected through questionnaire tests, and document analysis was analyzed by thematic analysis. The results show that the Neuromyth profile of the brain, learning, and teaching is not in accordance with scientific facts. For example, the notion that the left brain is more important and dominant for learning is compared to the left side. Judging from the multiple intelligences of PIAUD students, as many as 39.7% are at the level of naturalist intelligence. In conclusion, this Neuromyth profile needs to be overcome by providing accurate information about the brain, learning, and teaching, as well as using active and participatory learning methods reviewed from Education. The Multiple Intelligence of students is not related to neuro so there is no reason that multiple intelligence is related to neuroscience.